2020
DOI: 10.3390/f11121253
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Management of the Pine Processionary Moth in the North-Western Italian Alps

Abstract: The pine processionary moth (PPM), Thaumetopoea pityocampa (Denis and Schiffermüller, 1775) (Lepidoptera, Notodontidae), is considered one of the main insect defoliators of conifers in Southern Europe and North Africa. The species is oligophagous on pines and cedars in Mediterranean countries. This 6-year investigation (2014–2019), carried out in Aosta Valley (NW Italy), on Pinus sylvestris L. aimed to: (i) Monitor the PPM population with pheromone-baited funnel traps; (ii) assess the infestation index (0–5 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…However, the timing of application is always critical. In MD trials conducted in Aosta Valley (NW Italy) in 2016–2017, the number of males collected was significantly lower in the plots where MD was performed in comparison to control plots [ 199 ]. In addition, the total number of nests recorded per tree was significantly lower in MD plots.…”
Section: Application Of Insect Sex Pheromonesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the timing of application is always critical. In MD trials conducted in Aosta Valley (NW Italy) in 2016–2017, the number of males collected was significantly lower in the plots where MD was performed in comparison to control plots [ 199 ]. In addition, the total number of nests recorded per tree was significantly lower in MD plots.…”
Section: Application Of Insect Sex Pheromonesmentioning
confidence: 99%
“…In addition, the total number of nests recorded per tree was significantly lower in MD plots. The technique appears to be the most appropriate control strategy for the processionary moth, and address that repeated annual applications of MD could dramatically reduce population densities below the economic injury level [ 199 ].…”
Section: Application Of Insect Sex Pheromonesmentioning
confidence: 99%
“…The value of this ratio is 1.96 in the Sebdou station is in favor of the males. When the sex ratio is in favor of males, the potential of the Thaumetopoea pityocampa population is low (Ferracini et al, 2020;Questienne and Miermont, 1978). These results can be explained by the primordial action of climatic factors on the biology of the pine processionary, in particular that of the minimum temperatures in January and the annual sunstroke.…”
Section: Sex Ratiomentioning
confidence: 99%
“…These results can be explained by the primordial action of climatic factors on the biology of the pine processionary, in particular that of the minimum temperatures in January and the annual sunstroke. Ferracini et al (2020) has suggested over the years that the gradations of this pest were primarily linked to climatic factors. The aforementioned author notes that high or low temperatures can cause significant physiological disturbances, which can go as far as stopping feeding.…”
Section: Sex Ratiomentioning
confidence: 99%
“…Bacillus thuringiensis var. kurstaki (Btk), combined with mating disruption, are reported to be effective in controlling Thaumetopoea pityocampa Denis et Schiffermüller [27], a harmful insect for forest, urban and peri-urban pines, that needs to be kept under control because its larvae also cause public health problems for humans and pets. Finally, the use of Btk can also be integrated with other biological products, as proposed by Ruiu et al [28].…”
mentioning
confidence: 99%